If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 + -3x = 9 + -7x Solving 49 + -3x = 9 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 49 + -3x + 7x = 9 + -7x + 7x Combine like terms: -3x + 7x = 4x 49 + 4x = 9 + -7x + 7x Combine like terms: -7x + 7x = 0 49 + 4x = 9 + 0 49 + 4x = 9 Add '-49' to each side of the equation. 49 + -49 + 4x = 9 + -49 Combine like terms: 49 + -49 = 0 0 + 4x = 9 + -49 4x = 9 + -49 Combine like terms: 9 + -49 = -40 4x = -40 Divide each side by '4'. x = -10 Simplifying x = -10
| 5(x-7)=-2x+7 | | (3x-10)(8x-30)=180 | | 9w+4=5(w-8) | | (2x+3y)=3x | | 10+6h=34 | | 11x-10=(5x)-(9) | | 11/3=x-4/6 | | 7tanx+3=10tanx | | 1b+94a=94a | | 11x-10=5x-9 | | 5(5+7)=6(X+6) | | 24=(x*7)-(x*3) | | 10x+10y=2 | | 0.2x-2.9=2.9x+2.8 | | 1b+94a=24 | | e^1-5x=37 | | 2(x+6)-7= | | 8(7-1)=-24 | | 21=6g-9 | | 180=x(x-4)(x+9) | | (3c^2d^4)(-2c^2)= | | 0.25-2r=4 | | X(x-4)=4(x-5) | | 2x+46-3x= | | 2g+8=16 | | y+6=-9(x+10) | | 4x(10)2x-2=3x+4 | | a(n)=7+(n-1)(4) | | a(n)=7 | | -6+8(x-4)=12x+3-4x | | y+5=7(x+8) | | x(x+x)=4(4+5) |